Ethological and experimental approaches to behavior analysis: implications for ecotoxicology. - Cohn, J (1996)
Laboratory research in toxicology has progressed far beyond reliance on measures of mortality to make use of sophisticated behavioral preparations that can evaluate the consequences of sublethal toxicant exposure. In contrast, field studies have not evolved as rapidly. Approaches developed by experimental psychologists and ethologists provide powerful and complementary methodologies to the study of environmental pollutants and behavior. Observational data collection techniques can easily be used to broaden the number of questions addressed regarding sublethal exposure to toxic agents in both field and laboratory environments. This paper provides a background in such techniques, including construction of ethograms and observational methodologies, and the use of laboratory analogues to naturally occurring activities such as social behavior, predation, and foraging. Combining ethological and experimental approaches in behavior analysis can result in a more comprehensive evaluation of the effects of environmental contaminants on behavior.